A Systematic Literature Review on the Integration of Epistemological Theories in Educational Management Practices - Rifai, Alfan; Wachidi, Wachidi; Taqiyuddin, Yusuf Mukhtar; Haqiqi, Muh Adam; Ali, Mohammad (Universitas Muhammadiyah Surakarta, 2025)
The integration of epistemological theories into educational management has received limited scholarly attention, despite its potential to enhance the effectiveness and responsiveness of educational leadership, curriculum design, and policy-making. This study aims to systematically identify, analyze, and synthesize relevant literature on how key epistemological theories—namely constructivism, empiricism, rationalism, and pragmatism—are applied in the context of educational management. Using a qualitative Systematic Literature Review (SLR) approach, 40 peer-reviewed articles published between 2013 and 2023 were selected through a rigorous search in databases such as Scopus, Web of Science, ERIC, and ScienceDirect. The analysis was conducted using Braun and Clarke’s thematic analysis framework to extract dominant themes, trends, challenges, and conceptual implications. The findings show that epistemological integration influences strategic planning, teaching evaluation, institutional governance, and leadership development. Constructivist approaches foster participatory and reflective management practices; empiricism supports evidence-based decisions; rationalism emphasizes systematic reasoning; and pragmatism promotes contextual and flexible policy-making. However, institutional challenges such as epistemological illiteracy among decision-makers and the lack of cross-disciplinary dialogue limit broader implementation. This study offers a theoretical foundation and practical recommendations to embed epistemology into educational management, while also highlighting the need for further empirical research to operationalize these frameworks in diverse educational contexts.